Fast Food - Customer Perceptions And Responses Toward Value Of Marketing Mix In Fast Food Outlets - Hassan, Hasliza (2007)
This research studyfocuses on customer perceptions and response toward value of marketing mix in fast food outlets as a general. The research is developed based on systematic methodology in order to obtain excellent output from the analysis.